MENINGKATKAN KEMAMPUAN GURU KELAS DALAM MENCAPAI HASIL BELAJAR MATEMATIKA MELALUI MODEL QUANTUM TEACHING DI SD NEGERI 026408 BINJAI - Mida Mawarni Pasaribu (Universitas Islam Sumatera Utara, 2017)
This study aims to find out how to do the coaching ability of teachers to improve student learning outcomes Elementary School Mathematics 026 408 by using model study of Quantum Teaching. This research is a school action. The approach used in this study is a qualitative approach to the type of action research school. The subjects were 026 408 primary school teachers Binjai with number 6 teachers. Data from this study were collected through test results and the results of observation. Results lesson using Quantum Teaching methods result: On average Pre cycle learning outcomes in class was 55.00 so do the implementation of the first cycle with the average value obtained was 65.00, an increase of 10.00 and from the first cycle the second cycle to 65.00 into 90.00 is also an increase of 25.00. Thus in accordance with the criteria established that the model of Quantum Teaching can improve the learning outcomes of teachers on the subject of the rectangle.